The curious world of fluorinated molecules : molecules containing fluorine - Seppelt, Konrad, 1944- (Progress in fluorine science series., 2021)
The Curious World of Fluorinated Molecules: Molecules Containing Fluorine is the sixth volume in the Progress in Fluorine Science series and is edited by the world-renowned scientist Konrad Seppelt. Dr. Seppelt brings together a team of global experts to uncover the multifaceted nature of the most electronegative element in the Periodic Table. The book explores the fascinating world of unpredictable, fluorine-containing molecules through their discoveries, path to recognition, current state of the art, and impact on the broader fields of fluorinated materials development. This volume will inspire and energize researchers, future scientists, and educators working in fluorine chemistry.